THE DISTRIBUTION OF THE DEFENSE INDUSTRY IN THE LARGE ISLANDS IN RESPONSE TO THREATS IN THE JOINT DEFENSE AREA COMMAND WORKING AREA - Edwin, Edwin; DAW, Martinus (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2024)
The national defense industry is an industry that has high economic value in national development. Currently, the Indonesian defense industry continues to develop, producing defense equipment such as aircraft, drones, warships, combat vehicles, weapons, ammunition, missiles and components needed for defense. However, the existence of the defense industry is still concentrated on the island of Java. Indonesia, which has a very large land and sea area of ​​approximately 5,176,800 km2 and has potential military and non-military threats throughout the region, needs to carry out the distribution of industrial locations on large islands which can be used as a defense strategy and the mobilization of defense equipment and defense products quickly towards hot spots. Meanwhile, the joint defense area has also been divided into three, namely the Joint Defense Area Command (Joint Regional Defense Command) I, II and III. The division of the joint defense command area includes Joint Regional Defense Command I in western Indonesia, Joint Regional Defense Command II in central Indonesia and Joint Regional Defense Command III in eastern Indonesia. The defense industry is also balanced with a warehouse system for personnel provisions, operational provisions and maintenance provisions according to the defense area. The problem in this research is that there is no defense industry on the large islands in the Joint Regional Defense Command working area, which has become an obstacle in mobilizing logistics to face threats. The results of this research show the importance of distributing or deconcentrating the defense industry from Java to large islands in the Joint Regional Defense Command area so that it can respond to logistics mobilization to face threats. Keywords: Defense Industry, Distribution, Large Islands